The effects of process parameters on polydopamine coatings employed in tissue engineering applications - Sarkari, Soulmaz; Khajehmohammadi, Mehran; Davari, Niyousha; Li, Dejian; Yu, Baoqing (Frontiers in Bioengineering and Biotechnology, 2022)
The biomaterials’ success within the tissue engineering field is hinged on the capability to regulate tissue and cell responses, comprising cellular adhesion, as well as repair and immune processes’ induction. In an attempt to enhance and fulfill these biomaterials’ functions, scholars have been inspired by nature; in this regard, surface modification via coating the biomaterials with polydopamine is one of the most successful inspirations endowing the biomaterials with surface adhesive properties. By employing this approach, favorable results have been achieved in various tissue engineering-related experiments, a significant one of which is the more rapid cellular growth observed on the polydopamine-coated substrates compared to the untreated ones; nonetheless, some considerations regarding polydopamine-coated surfaces should be taken into account to control the ultimate outcomes. In this mini-review, the importance of coatings in the tissue engineering field, the different types of surfaces requiring coatings, the significance of polydopamine coatings, critical factors affecting the result of the coating procedure, and recent investigations concerning the applications of polydopamine-coated biomaterials in tissue engineering are discussed in detail.